Copper Coordination Compounds as Corrosion-Resistant Materials for Seawater Electrolysis - Jimenez-Arevalo, V; Jimenez-Arevalo, V (Multidisciplinary Digital Publishing Institute (MDPI), 2026)
Seawater electrolysis offers a promising route for sustainable hydrogen production in coastal areas, leveraging solar energy while reducing freshwater consumption. Yet, chloride-induced corrosion severely limits conventional electrodes such as titanium, which depend on passive titanium dioxide films and display minimal hydrogen evolution reaction activity (|i0,H2| ≈ 0.001–0.01 A/m2). Here, we report for the first time the use of copper-based coordination compounds—a triazole-derived polymer (CCCu) and a Prussian Blue Analogue (CuHCF)—as dual-function electrodes combining corrosion resistance with electrocatalytic activity. Structural integrity was verified by FTIR, TGA, XRD, and SEM/EDS analyses. Electrochemical tests in 0.5 M NaCl, interpreted using mixed potential theory, revealed corrosion potentials (Ecorr) of −40 mV versus Standard Hydrogen Electrode (CuHCF) and −23 mV versus Standard Hydrogen Electrode (CCCu), and corrosion current densities of 0.259 and 0.379 A/m2, respectively. Both exhibited hydrogen evolution reaction exchange current densities significantly higher than titanium (0.019 A/m2 for CuHCF and 0.062 A/m2 for CCCu). CuHCF achieved a Tafel slope of 222 mV/dec, comparable to NiMoP alloys and carbon steel. Complementary density functional theory calculations elucidated how metal–ligand interactions and electronic redistribution govern both catalytic performance and degradation. These findings introduce a new concept of semi-electrocatalysts, where copper coordination compounds act as structurally adaptive, low-cost materials bridging corrosion resistance and hydrogen evolution in seawater systems. © 2026 by the authors.